MO308: Urinary Biomarkers to Predict Acute Kidney Damage and Mortality In COVID-19. (3rd May 2022) - Racovitan, Diana; Hogeweg, Maximilian; Doevelaar, Adrian; Seidel, Maximilian; Rohn, Benjamin; Bettag, Sebastian; Rieckmann, Sonja; Babel, Nina; Henning Westhoff, Timm; Seibert, Felix S
Abstract: BACKGROUND AND AIMS: Acute kidney injury (AK) is a frequent condition in patients hospitalized for COVID-19. There are only few reports on the use of urinary biomarkers in COVID-19 and no data comparing the prognostic use of individual biomarkers in the prediction of adverse outcome so far. METHOD: We performed a prospective monocentric study on the value of urinary biomarkers to predict the composite endpoint of a transfer to the intensive care unit (ICU), the need for renal replacement therapy (RRT), mechanical ventilation and in-hospital mortality. A total of 41 patients hospitalized for COVID-19 were enrolled in this study. Urine samples were obtained shortly after admission in order to assess neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), calprotectin and vanin-1. RESULTS: We identified calprotectin as a predictor of a severe course of the disease, requiring intensive care treatment (AUC 0.728, P = .016). Positive and negative predictive values were 78.6% and 76.9%, respectively, using a cut-off concentration of 127.8 ng/mL. NGAL tended to predict COVID-19 associated AKI without reaching statistical significance (AUC 0.669, P = .053). The best parameter in the prediction of in-hospital mortality was NGAL as well (AUC 0.674, P = .077). KIM-1 and vanin-1 did not reach significance for any of the investigated endpoints. CONCLUSION: While KIM-1 and vanin-1 did not provide prognostic clinical information in the context of COVID-19, this study shows that urinary calprotectin and NGAL concentrations are independent predictors of an adverse course of the disease. Calprotectin and NGAL may thereby constitute helpful adjuncts in the identification of patients at increased risk who may benefit from upcoming antiviral agents to SARS-CoV-2.